Nonlinear Variability of Body Sway in Patients with Phobic Postural Vertigo - Schniepp, Roman; Wuehr, Max; Pradhan, Cauchy; Novozhilov, Sergej; Krafczyk, Siegbert; Brandt, Thomas; Jahn, Klaus (Frontiers in Neurology, 2013)
Background: Subjective postural imbalance is a key symptom in the somatoform phobic postural vertigo (PPV). It has been assumed that more attentional control of body posture and/or co-contraction of leg muscles during standing is used to minimize the physiological body sway in PPV. Here we analyze nonlinear variability of body sway in patients with PPV in order to disclose changes in postural control strategy associated with PPV. Methods: Twenty patients with PPV and 20 age-matched healthy controls were recorded on a stabilometer platform with eyes open, eyes closed and while standing on a foam rubber with eyes closed. Spatio-temporal changes of the center of pressure (CoP) displacement were analyzed to assess the structure of postural variability by computing the scaling exponent α and the sample entropy (SEn) of the time series. Results: With eyes open on firm ground α and SEn of CoP displacement were significantly lower in patients (p < 0.001). For more difficult conditions (eyes closed, standing on a foam rubber) postural variability in PPV assimilated to that of healthy controls. Conclusions: Postural control in PPV patients differs from controls under normal stance condition. It is characterized by a reduced scaling behavior and higher regularity. These changes in the structure of postural variability might suggest an inappropriate attentional involvement with stabilizing strategies, which are used by healthy subjects only for more demanding balance tasks.